ORGANIZATIONAL CULTURE AND CYBERLOAFING: ASSESSING THEIR IMPACT ON HOSPITAL EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION - Widias Asmara, Ratna; Anang Kistyanto; Dewie Tri Wijayati Wardoyo (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: The study examines the effects of organizational culture and cyberloafing behavior on employee performance, with job satisfaction as a mediating variable, at RSUD dr. Sayidiman Magetan. Purpose: The main objective of this research is to determine how organizational culture and cyberloafing behavior influence employee performance, considering job satisfaction as an intermediary factor. Novelty: This research uniquely integrates the mediating role of job satisfaction in the relationship between organizational culture, cyberloafing behavior, and employee performance within a hospital setting. Research Methods: A quantitative approach was employed, involving 216 employees of RSUD dr. Sayidiman Magetan as respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. Results: Organizational culture positively and significantly impacts employee performance and job satisfaction. Cyberloafing behavior negatively and significantly affects employee performance and job satisfaction. Job satisfaction positively and significantly influences employee performance. Organizational culture positively affects employee performance through job satisfaction. Cyberloafing behavior negatively impacts employee performance through job satisfaction. Research Contributions: These results provide significant insights for the management of RSUD dr. Sayidiman Magetan, emphasizing the importance of fostering a supportive organizational culture and reducing cyberloafing behavior to enhance employee performance